The upper limit : how low-wage work defines punishment and welfare - Bonnet, François, 1979- (University of California Press, 2019)
"Since 1993, crime has fallen in the United States to historical lows, providing extraordinary legitimacy to the country's peculiar mix of welfare and punishment, with ever stingier social programs for the poor and the highest rates of incarceration in the world. The Upper Limit sets out to explain why. It provides a comprehensive theory of the evolution of social and penal policy which can be summarized thus: welfare has to be less attractive than low-wage work, and punishment has to make criminal life less attractive than welfare. Low-wage work sets the upper limit of social and penal policy. Declining living standards for the poor since the 1970s have lowered the upper limit in the United States. The Upper Limit explores how these transformations and the ensuing crime drop have affected the lives of the poor in a formerly high-crime Brooklyn neighborhood, East New York. It explains the dark logic behind police brutality, the trials of prisoner reentry and the inhumanity of New York's homeless shelters"--Provided by publisher.